Personal approach to communities of Natives help boosts pursuit of tertiary education - UMP, PNC (2019)
In line with the vision to promote “School for the Community” and “University for the Society”, the Ministry of Education (MoE) is committed to undertake a more personal approach to propagate information about opportunities in pursuit of higher and tertiary education to the Malaysian Natives, based on the former’s three core values and embedded culture – love, happiness and mutual respect.